The Geographies of Precarious Labour in Canada - Ali, Waad; Newbold, K.; Mills, Suzanne (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2020)
Using Statistics Canada’s 2011-2016 Labor Force Surveys, this paper examines the spatial dimensions of precarious forms of employment (PFE) in Canada. We first compare different PFEs across a range of geographies including national, provincial, census metropolitan areas and urban/rural areas. The results show that different PFEs exhibited distinct spatial patterns across space and scale. Second, using logistic regression models, results show that patterns in PFEs were reinforced by factors such as immigration status, gender, age, education, and income. These models further confirm that spatial variations in PFEs were robust even when controlling for socio-demographic and socio-economic effects. Taken together, these marked spatial patterns advances our understanding of the spatial divisions of precariousness in Canada.